PUBLIC DEBT AND ECONOMIC CYCLE (Research Bulletins of the Faculty of Economic Sciences, 2021)
The aim of this article is to present the problem of public debt, especially rising amount of this. This dangerous direction was observed for years and it accelerated in recession time. What is more, growing countries indebtednessis a sign of temporary public finance and it makes difficult to prevent the future crisis and shocks because it limits possibilities ofbudgetary policy. First part of this work was dedicated to describe correlation between economic cycle and level of public debt. In the second piece, there was highlighted fact that public indebtednessis rising irrespective to growing GDP, what may be very interesting to future research.Finally conclusion suggests that influ-ence of GDP growth on indebtedness level depends on budgetary policy restrictiveness.
Keywords: economic situation, public debt, budget deficit, GDP growth, financialaccount, paradox of an unbalanced budget